Lifestyle and Cancer Prevention—Opinions and Behaviors Among Romanian University Students - Lotrean, Lucia Maria (Int J Gen Med, 2021)
BACKGROUND: Healthy lifestyle promotion represents an important component of cancer prevention. The aim of this study is the assessment of opinions and behavior related to healthy lifestyle and cancer prevention among Romanian university students. METHODS: A cross-sectional study was performed by anonymous questionnaires in 2017 among 400 university students from the four main universities from Cluj-Napoca, Romania. RESULTS: One out of five students was overweight or obese, but 83% meet the recommendations for performing physical activity. The majority did not meet the recommendations of eating 400 g of fruits and vegetables daily, while almost half declared eating more than 500 g of red meat weekly and more than one third do not respect the recommendations for alcohol consumption. The factor analysis reveals two factors with regard to cancer prevention-related behaviors. The first one consists of those having an appropriate body weight, and having a higher tendency for consumption of fruits and vegetables, performing physical activity, while being more prone not to respect the recommendations regarding the alcohol consumption. The second factor refers to a higher tendency to respect both the recommendations for alcohol and red meat consumption. CONCLUSION: Future educational activities should focus on promoting better nutritional habits, decrease alcohol consumption and offer appropriate services for weight management among Romanian university students.